Complexities in understanding attentional functioning among children with fetal alcohol spectrum disorder - Lane, Kimberly; Stewart, Jillian; Fernandes, Tania; Russo, Natalie; Enns, James T.; Burack, Jacob A. (Frontiers in Human Neuroscience, 2014)
Parental reports of attention problems and clinical symptomatology of ADHD among children with fetal alcohol syndrome disorder (FASD) were assessed in relation to performance on standardized subtests of attantional control/shifting and selective attention from the Test of Everyday Attention for Children (TEA-Ch; Manly et al., 1998). The participants included 14 children with FASD with a mean CA of 11.7 years and a mean MA of 9.7 years, and 14 typically developing (TD) children with no reported history of prenatal exposure to alcohol or attention problems with a mean CA of 8.4 years and a mean MA of 9.6 years. The children with FASD were rated by their caregivers as having clinically significant attention difficulties for their developmental age. The reported symptomatology for the majority of the children with FASD were consistent with a diagnosis of ADHD, combined type, and only one child had a score within the average range. These reports are consistent with the finding here that the children with FASD demonstrated difficulties on the Creature Counting subtest of attentional control/shifting, but inconsistent with the finding that they outperformed the TD children on the Map Mission subtest of selective attention. These findings are considered within the context of the complexity in understanding attentional functioning among children with FASD and discrepancies across sources of information and components of attention.